ANALISIS KARAKTERISTIK DAN PENANGANAN BAGI ANAK BERKEBUTUHAN KHUSUS (AUTISME) DI SEKOLAH KHUSUS HARAPAN NEGERI 01 KOTA SERANG - Yahdinil Firda Nadhirah; Fauzan Nazil Ramadhan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Autistic children are children with complex learning difficulties that affect a wide range of functions, including perception, intention, imagination and feelings. This difficulty usually appears before the age of three and is caused by a lack of statistical evidence in social interaction, communication, and problem solving in one activity or object so that it requires special education services to maximize potential. This study aims to determine the characteristics of children with special needs, namely autism in the special school of hope of the state 01 city of serang and how to handle children with special needs, namely autism in the school. The method used in this research is a qualitative method using field observation techniques and interviews with students and teachers who teach these students. The results showed that the characteristics of autistic children in the special school of Harapan Negeri 01 Kota Serang varied from difficulties in communicating verbally and non-verbally, difficulties in understanding the feelings and views of others, and so on, while the handling of autistic children in the school, the principal made a curriculum design that was not only intended for learning material, but also for handling the social interaction skills of autistic children.